MARKETING COMMUNICATIONS OF CATFISHES (Clarias sp) CULTIVATOR IN HANG TUAH VILLAGE PERHENTIAN RAJA SUBDISTRICT, KAMPAR REGENCY RIAU PROVINCE - Nining Sumiarti; Zulkarnain Zulkarnain; Darwis AN Darwis AN (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT               Marketing communication has a very important role for businesses to introduce certain products. This study aims to determine the marketing communications of Catfishes (Clarias sp) cultivator and determine the constraints faced by Catfishes (Clarias sp) cultivator in the Hang Tuah Village. This study was conducted on April, until May 2019 in Hang Tuah Village Perhentian Raja Subdistrict, Kampar Regency Riau Province. The method used is the Grounded Theory method by conducting a qualitative approach, where the determination of informants by Snowball Sampling with 12 informants.The result showed that of marketing communications effective used of Catfishes (Clarias sp) cultivator is by using mix communication Public Relation introduce Hang Tuah Village communities to be attracted to visit Hang Tuah Village. Constraints that have been of Catfishes (Clarias sp) cultivator Hang Tuah Village, cultivation of the a place far, not the cooperatives to the business of Catfishes (Clarias sp) cultivator, cultivator of the still doing cultivation simply, reduced cultivation results at certain times and promotion is still low.Keywords: Communication, Marketing, Cultivator Of The Catfishes